2007
DOI: 10.1017/s1047951107001448
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of stents for treatment of recurrent and native coarctation in children weighing less than 20 kilograms

Abstract: We report our experience with implantation of stents for treatment of recurrent and native aortic coarctation in children weighing less than 20 kilograms. We treated 9 such patients between March, 2003, and January, 2006. In 2 patients, the coarctation had not previously been treated, while in 7 it had recurred after surgery. The patients had a median weight of 14 kilograms, with a range from 5.5 to 19 kilograms. Balloon dilation was needed in 1 patient before the stent was implanted. We used Palmaz Genesis XD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Golden and Hellenbrand (2), in their review of the Congenital Cardiovascular Interventional Study Consortium data consisting of 588 stent placements for CoA in children and adults from 17 centers, report only 7% (40 of 588) of the patients were under 6 years of age. Schaeffler et al (24) reported 9 patients with a median weight of 14 kg (range 5.5 to 19 kg) who underwent successful stent placement for CoA. In our study, we report 22 patients with a median weight of 20.7 kg (range 9.7 to 27 kg).…”
Section: Discussionmentioning
confidence: 58%
“…Golden and Hellenbrand (2), in their review of the Congenital Cardiovascular Interventional Study Consortium data consisting of 588 stent placements for CoA in children and adults from 17 centers, report only 7% (40 of 588) of the patients were under 6 years of age. Schaeffler et al (24) reported 9 patients with a median weight of 14 kg (range 5.5 to 19 kg) who underwent successful stent placement for CoA. In our study, we report 22 patients with a median weight of 20.7 kg (range 9.7 to 27 kg).…”
Section: Discussionmentioning
confidence: 58%
“…This report contains the largest reported series of stent redilation procedures for COA [6, 8–11]. Of the 28 attempts during the study period, 26 attempts (93%) were successful.…”
Section: Discussionmentioning
confidence: 99%
“…In the older child, adolescent and adult, primary stent therapy is advised both for native aortic coarctation and post-surgical recoarctation. Because of issues related to growth and the need for large sheaths for implantation, most cardiologists limit stent usage to adolescents and adults, although some workers [15,105,[111][112][113][114] advocate stents in infants and young children. We do not advocate routine use of stents in neonates, infants and young children [106,115].…”
Section: Indicationsmentioning
confidence: 99%